2023
DOI: 10.1002/marc.202300039
|View full text |Cite
|
Sign up to set email alerts
|

An Unconventional Route for Synthesis and Solid‐State Processing of Low‐Entangled Ultra‐High Molecular Weight Isotactic Polypropylene

Abstract: Introducing the reverse micelle formation during polymerization, and thus avoiding the catalyst support, aggregated single crystals of ultra‐high molecular weight isotactic polypropylene having spherical morphology are obtained. The ease in flowability of the spherical nascent morphology, having a low‐entangled state in the non‐crystalline region of the single crystals in the semi‐crystalline polymer, allows the sintering of the nascent polymer in the solid state without melting. Thus maintains a low‐entangled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Based on previous knowledge acquired by our group on UHMW-polyethylene and UHMW-isotactic polypropylene, it can be anticipated that the ability of processing the polymer below the melting point is attributed to a lower degree of entanglement in the noncrystalline region of the semicrystalline polymer. 36,51 Such an opportunity provides a possible method to process a brittle material such as PLA (without melting or dissolution in organic solvents) via an environmental-friendly route, thus avoiding/reducing thermally activated chain degradation (hydrolysis), a common challenge in melt processing of aliphatic polyesters. The Figure 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous knowledge acquired by our group on UHMW-polyethylene and UHMW-isotactic polypropylene, it can be anticipated that the ability of processing the polymer below the melting point is attributed to a lower degree of entanglement in the noncrystalline region of the semicrystalline polymer. 36,51 Such an opportunity provides a possible method to process a brittle material such as PLA (without melting or dissolution in organic solvents) via an environmental-friendly route, thus avoiding/reducing thermally activated chain degradation (hydrolysis), a common challenge in melt processing of aliphatic polyesters. The Figure 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another fundamental aspect of interest in achieving the crystallization of the PLA during synthesis is the possibility of decreasing chain overlap (entanglement) during polymer growth, thus accessing the low entangled state. If chain overlap is decreased and the polymer produced has a lower amount of entanglement, then uniaxial orientation below the melting point (without any solvent) is feasible, as demonstrated for ultrahigh-molecular-weight (UHMW)-polyethylene and UHMW- isotactic -polypropylene . This processing route allows the production of fibers or tape without the need to melt the material.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the average size of the particles increases from 0.9 μm in 2 h to 1.6 μm after reacting for 13 h. Increasing the polymerization time to 24 h resulted in the micro flowers type morphology build-up with interstacked petals having an average size of 4.2 μm. Similar “flower-like” morphology on low-entangled ultrahigh molecular weight polyethylene (dis-UHMWPE) and low-entangled ultrahigh molecular weight isotactic polypropylene is reported while using postmetallocene single-site catalyst systems. , The average size of the crystalline nascent particles is observed to be increasing with increasing reaction time (0.9–4.2 μm), as the molecular mass of the isolated polymer also shows a progressive increase from 1.3 × 10 5 to 4.0 × 10 5 g mol –1 (entries 1, 2, 3, and 4, Table S1, Supporting Information section). At a higher reaction temperature, at 60 °C (entry 2, Table ), the highly ordered crystalline morphology, which is found at the low polymerization temperature of 25 °C, is disrupted, and more porous-like structures (Figure d) are formed.…”
Section: Resultsmentioning
confidence: 99%
“…Rastogi et al reported 65 the synthesis of the ultrahigh-molecular-weight polyethylene and isotactic-polypropylene. 66 At lower polymerization temperature and lower catalyst concentration, the crystallization rate is higher than the polymerization rate, and folded chain crystals with less entanglement are produced. The present work first showed a new route to synthesize the less entangled high-molecular-weight trans-1,4-PBD (1,4-t-PBD) with M w = 500 kg/mol under tailored polymerization conditions using a homogeneous catalyst and the formation of single crystals during polymerization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides the solution crystallization, varying the polymerization conditions is a more advanced method to produce polymer with high-molecular weight and less entanglement density in the amorphous region. Rastogi et al reported the synthesis of the ultrahigh-molecular-weight polyethylene and isotactic -polypropylene . At lower polymerization temperature and lower catalyst concentration, the crystallization rate is higher than the polymerization rate, and folded chain crystals with less entanglement are produced.…”
Section: Introductionmentioning
confidence: 99%